Development of Ocean Energy Technologies: A Case Study of China. (4th November 2013) - Guodong, Qin; Ping, Lou; Xianglian, Wu
Abstract : For the energy shortage in China's coastal areas, which has exerted severe impact on economy development, a growing number of attentions have been paid to ocean energy utilization. In this paper, a review of related researches as well as development of ocean energy in China is given. The main part of this paper is the investigation into ocean energy distribution and technology status of tidal energy, wave energy, and thermal energy, especially that of the tidal energy and wave energy. Finally, some recommendations for the future development of ocean energy in China are also provided. For further research in this field and development of ocean energy utilization in China, this review can be taken as reference.